Evaluation of confirmatory data following the Article 12 MRL review for chlorothalonil, including assessments for import tolerances for banana, papaya and peanuts. (28th September 2020) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; et al.
Abstract: The applicants Syngenta Crop Protection, UPL Europe Ltd. and Oxon Italia S.p.A. submitted requests to the competent national authority in the Netherlands to evaluate the confirmatory data for chlorothalonil that were identified in the framework of the MRL review under Article 12 of Regulation (EC) No 396/2005 as not available; in addition, Syngenta and UPL submitted requests for modifications of existing MRLs. Considering the recent decision on the non‐approval of chlorothalonil, the requests for amending existing MRLs to reflect intended EU uses for chlorothalonil and confirmatory data for EU uses became obsolete. EFSA focused therefore its assessment on the import tolerances and on general information on the analytical method required to enforce legal limits for chlorothalonil and its metabolite SDS‐3701 (R182281). Analytical methods for enforcement are available to control the residues of chlorothalonil and SDS‐3701 in plant matrices at the validated LOQ of 0.01 mg/kg; data on the extraction efficiency for high oil content matrices as requested in the MRL review were not provided. This data gap is relevant for the import tolerance for peanuts. The data submitted in support of import tolerances were found to be sufficient to derive MRL proposals for chlorothalonil and SDS‐3701 for bagged bananas, papayas and peanuts. Studies investigating the effect of high temperature processing on the magnitude of SDS‐3701 in processed products are not available. Based on exposure calculations for chlorothalonil, EFSA concluded that the long‐term intake of residues resulting from the use of chlorothalonil according to the reported agricultural practices is unlikely to present a risk to consumers. For papaya, an acute intake concern was noted for chlorothalonil, while for banana and peanuts, the expected short‐term intake of chlorothalonil residues was below the toxicological reference value. For the metabolite SDS‐3701, the toxicological profile is not fully elucidated, and therefore, toxicological reference values could not be derived. Hence, for this metabolite, the consumer risk assessment cannot be finalised.